A fusion protein derived from plants holds promising potential as a new oral therapy for type 2 diabetes. Issue 4 (30th December 2013) - Choi, Jeehye; Diao, Hong; Feng, Zhi‐Chao; Lau, Arthur; Wang, Rennian; Jevnikar, Anthony M.; Ma, Shengwu
Summary The incretin hormone glucagon‐like peptide‐1 (GLP‐1) is recognized as a promising candidate for the treatment of type 2 diabetes (T2D), with one of its mimetics, exenatide (synthetic exendin‐4) having already been licensed for clinical use. We seek to further improve the therapeutic efficacy of exendin‐4 (Ex‐4) using innovative fusion protein technology. Here, we report the production in plants a fusion protein containing Ex‐4 coupled with human transferrin (Ex‐4‐Tf) and its characterization. We demonstrated that plant‐made Ex‐4‐Tf retained the activity of both proteins. In particular, the fusion protein stimulated insulin release from pancreatic β‐cells, promoted β‐cell proliferation, stimulated differentiation of pancreatic precursor cells into insulin‐producing cells, retained the ability to internalize into human intestinal cells and resisted stomach acid and proteolytic enzymes. Importantly, oral administration of partially purified Ex‐4‐Tf significantly improved glucose tolerance, whereas commercial Ex‐4 administered by the same oral route failed to show any significant improvement in glucose tolerance in mice. Furthermore, intraperitoneal (IP) injection of Ex‐4‐Tf showed a beneficial effect in mice similar to IP‐injected Ex‐4. We also showed that plants provide a robust system for the expression of Ex‐4‐Tf, producing up to 37 μg prEx‐4‐Tf/g fresh leaf weight in transgenic tobacco and 137 μg prEx‐4‐Tf/g freshweight in transiently transformed leaves of N. benthamiana. These results indicate that Ex‐4‐Tf holds substantial promise as a new oral therapy for type 2 diabetes. The production of prEx‐4‐Tf in plants may offer a convenient and cost‐effective method to deliver the antidiabetic medicine in partially processed plant food products.